ASEAN Way: Managing Expectation in the Code of Conduct for the South China Sea - Lardo, Naifa Rizani (Global: Jurnal Politik Internasional, 2021)
Pessimistic perspectives on the ASEAN Way process frequently undermine the role of the Association of Southeast Asian Nations (ASEAN) in resolving the South China Sea (SCS) dispute. These justifications are addressed through the notion of power balance, which undermines the norm institutionalism framework that underlines the ASEAN Way’s foundation. This droves various conversations on ASEAN capabilities ahead of the ASEAN Way principle throughout the Code of Conduct for the South China Sea (COC for SCS) process, which questioned its expectations as a regional security body. This article offers insight on ASEAN’s regional security role in the SCS dispute peace process, guided by the question “What to expect from ASEAN Way in the process of COC for SCS?” Instead of following the power balance approach, this article suggests a norm-based institutionalism perspective through ASEAN Way to the COC process. The ASEAN Way was developed to facilitate security cooperation under flexible participation among relevant parties involved in the conflict. The ASEAN Way on COC for SCS contributes by allowing relevant actors to engage in peaceful dialogue despite the power imbalance that existed on the disputed sea. This flexible participation offered by ASEAN can deliver cooperative security to the Southeast Asia region in the interest of peace. Nonetheless, norm institutionalism also revealed limitations in ASEAN capability that impede the expectation of the formulation of COC for SCS to the resolution of SCS disputes.